Packaging Ethics: Perceptual Differences among Packaging Professionals, Brand Managers and Ethically-interested Consumers - Bone, Paula Fitzgerald (Journal of business ethics, 2000)
In this article, we explore ethical perceptions of three product packaging issues as viewed by packaging professionals, brand managers, and ethically-interested consumers. We examine, differences between business practitioners and consumers with respect to ethical sensitivity, perceived consequences of business practices, and perceived industry norms. Additionally, we explore the prevalence of two types of values, pragmatic and moral, to determine if the use of these value-types differs among the three groups. We find that business practitioners exhibit less ethical sensitivity. Businesspeople also feel that the likelihood and severity of negative consequences resulting from a packaging practice is lower than do ethically-interested consumers. Finally, business practitioners do not differ from consumers with respect to moral values.